Effects of Inclusion of Fermented Carrageenan By-products in the Basal Diet of Broiler Chickens on Growth Performance, Blood Profiles and Meat Composition - Hasanuddin, Asriani; Rusdi,; Arief, Rosmiaty (International Journal of Poultry Science, 2017)
Background: Carrageenan by-products may be a potential source of nutrients that may improve the health and growth performance of broiler chickens. Objective: This study aimed to evaluate the effects of fermented carrageenan by-products (FCB) on the growth performance, blood profiles and meat composition of broilers. Methodology: Two hundred and fifty one day old chicks (DOC) were distributed in a completely randomized design consisting of 5 treatments and 5 replicates with 10 birds per replicate. The basal diet mainly consisted of corn, soybean, rice bran and fish meal and the treatments were T1 (basal diet only as a control), T2 (97.5% basal diet+2.5% FCB), T3 (95.0% basal diet+5% FCB), T4 (92.5% basal diet+7.5% FCB) and T5 (90.0% basal diet+10% FCB). Experimental birds were kept under standard management conditions for 5 weeks. Results: The inclusion of FCB in the basal diet significantly affected feed intake, Body Weight Gain (BWG) and Feed Conversion Ratio (FCR) and it significantly reduced the concentration of blood cholesterol, triglycerides and Low Density Lipoproteins (LDL) while significantly elevating High Density Lipoproteins (HDL). However, blood haemoglobin values were statistically similar among all treatments. Furthermore, FCB significantly reduced the fat and cholesterol content of the breast meat but did not significantly affect the water, protein and ash contents. Conclusion: Up to 7.5% FCB can be used in broiler chicken diets to improve growth performance and the quality of the breast meat.